Trade Imbalances, Export Structure and Wage Inequality. (May 2014) - Crinò, Rosario; Epifani, Paolo
<x xml:space="preserve">Abstract</x> We study, both theoretically and empirically, how trade imbalances affect the structure of countries' exports and wage inequality. We show that, in a Heckscher–Ohlin model with a continuum of goods, a Southern (Northern) trade surplus leads to an increase (reduction) in the average skill intensity of exports, in the relative demand for skills and in the skill premium in both countries. We provide robust support for the mechanism underlying these predictions using a large panel of countries observed over the past 30 years. Our results suggest that the large and growing North–South trade imbalances arisen over the last three decades may have exacerbated wage inequality worldwide.